2023
DOI: 10.1097/iae.0000000000003769
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vasculitis or Vascular Occlusion After Brolucizumab for Neovascular Age-Related Macular Degeneration

Abstract: Complement inhibition for the treatment of geographic atrophy results in a slowing of expansion of a surrogate marker but has no proven effect on functional outcome measures in randomized trials. Subjecting patients to treatments with expense and risk of side effects is not balanced out by any expected gain in function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
(75 reference statements)
2
7
1
Order By: Relevance
“…IOI events' onset occurred early, within the rst to the third brolucizumab injection and 7 to 21 days after the last injection (Table 1), which is in accordance with the OCTOPUS and SWIFT trials or in line with a recent review reporting 88% of cases within 30 days, after a mean of 1.7 brolucizumab injections before the event 2,17 . The time to discharge from 2 to 9 weeks, longer when RO was present, was slightly less than what was found in the aforementioned trials.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…IOI events' onset occurred early, within the rst to the third brolucizumab injection and 7 to 21 days after the last injection (Table 1), which is in accordance with the OCTOPUS and SWIFT trials or in line with a recent review reporting 88% of cases within 30 days, after a mean of 1.7 brolucizumab injections before the event 2,17 . The time to discharge from 2 to 9 weeks, longer when RO was present, was slightly less than what was found in the aforementioned trials.…”
Section: Discussionsupporting
confidence: 86%
“…Brolucizumab is a humanized monoclonal antibody single-chain variable fragment, which pro ciently inhibits all variants of VEGF-A 1 . Its desirable attributes, such as its small molecular weight and excellent solubility, have rendered it immensely attractive to ophthalmologists since these qualities allow the administration of higher doses at longer intervals between intravitreal injections 2 . It was approved on October 7, 2019 by the US Food and Drug Administration (FDA) at a dosage of 6 mg for the treatment of neovascular age-related macular degeneration (nAMD) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The current analysis also showed that the risk of an IOI, RV, and/or RO event was affected by age, sex, and prior anti-VEGF therapy. Eyes from male patients were significantly less likely to experience an event than those from female patients, in line with the earlier IRIS Registry and Komodo database findings [ 6 ] and the high proportion of female cases in real-world studies [ 4 , 19 , 20 ]. Furthermore, while the earlier IRIS Registry and Komodo database analysis showed that age and prior anti-VEGF therapy were not associated with an increased risk of any form of IOI and/or RO, the current analysis suggests that treatment-naive eyes were less likely to experience an event than those with prior anti-VEGF therapy and that older age was associated with a reduced risk of an event [ 6 ].…”
Section: Discussionsupporting
confidence: 83%
“…Despite its efficacy, brolucizumab carries an elevated risk of intraocular inflammation that has limited its use. 40 The ranibizumab port delivery system (PDS) is a refillable intravitreal device that is surgically implanted and offers sustained release of drug over 24 weeks. 21 This system has the benefit of avoiding the need for frequent intravitreal injections.…”
Section: Faricimab: Tenaya Lucerne Faretina-amd Truckeementioning
confidence: 99%